Tone Moves. A History of Piano Technique - Chiantore, Luca (Barcelona Musikeon, 2019)
In this book the musicologist and pianist Luca Chiantore shows the two main facets of his activity, in which piano technique is a constant field of study and at the same time the starting point for fascinating artistic proposals. The new English version of his already classic «Historia de la técnica pianística» is a reference book on the subject.
Keywords: Piano; Music history; Music education; Musical interpretation